Micro-Finance in Krishnagiri District:A Tool for Poverty Alleviation - Saraswathy, A.; Porkodi, S.; Bhuvaneswari, M. (Indian Journal of Marketing, 2009)
Globally, Micro Finance (MF) has been recognized as a powerful instrument to address poverty. Beyond the direct link with poverty reduction, it is an indirect link to address the issues of health, education, gender. The task force would like to emphasis in its definition that MF will cover not only consumption & production loans, but will also include other credit needs such as housing & shelter improvement; while other financial services like savings and insurance are also included under it. It may be left to the MFIs (Micro Finance Institutions) to identify the poor. Thus, MFI is an organization that provides financial services to the poor. "Provision of thrift, credit & other financial services & products of very small amounts to the poor in rural, semi-urban or urban areas for enabling them to raise their income levels & improving living standards".